Penerapan Kewenangan POLRI Melakukan Penegakan Hukum Terhadap Pelaku Pidana Penambangan Batu Bara Illegal - Fahrurrozi, Fahrurrozi; Said, Yusuf Muhamad (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2022)
Indonesia is a country rich in minerals (mining). The minerals contained in the form of gold, silver, copper, oil and natural gas, coal and many other natural potentials that can support the development of the country. All mining materials are controlled by the state and used for the entire Indonesian nation, based on the fifth principle of Pancasila as a unified whole, the existence of norms or rules in the provisions of Article 33 Paragraph (3) of the 1945 Constitution of the Republic of Indonesia. “Earth, water and natural resources contained therein shall be controlled by the State and used for the greatest prosperity of the people." All natural wealth and its contents are controlled by the state and used for the prosperity of the people, the Indonesian people should not experience a permanent spike in poverty, if the state apparatus including prosecutors and judges consistently carry out crackdown on illegal mining. In the field, there was a disparity in demands and decisions that were quite favorable to the defendant, as found in this study. The type of research is carried out with a normative juridical approach, research that prioritizes library data, namely research on secondary data. Secondary data can be in the form of primary, secondary or tertiary legal materials, such as positive legal provisions that apply in Indonesia relating to law enforcement against perpetrators of illegal coal mining crimes, and data obtained from research results obtained directly on the object. research, literature, is carried out with research that is literature in nature to search for, find and use materials regarding conceptions, theories, or expert opinions related to the problems that are the object of research, such as Primary Law materials, the Criminal Code, the Mining Law No. 3 of 2020, secondary and tertiary law materials, namely dictionaries and magazines that discuss the object of research.